The Effects of a 6-Week Strength Training on Critical Velocity, Anaerobic Running Distance, 30-M Sprint and Yo-Yo Intermittent Running Test Performances in Male Soccer Players - Karsten, Bettina (PLoS One, 2016)
The objectives of this study were to examine the effects of a moderate intensity strength training on changes in critical velocity (CV), anaerobic running distance (D'), sprint performance and Yo-Yo intermittent running test (Yo-Yo IR1) performances. Methods: two recreational soccer teams were divided in a soccer training only group (SO; n = 13) and a strength and soccer training group (ST; n = 13). Both groups were tested for values of CV, D', Yo-Yo IR1 distance and 30-m sprint time on two separate occasions (pre and post intervention). The ST group performed a concurrent 6-week upper and lower body strength and soccer training, whilst the SO group performed a soccer only training. Results: after the re-test of all variables, the ST demonstrated significant improvements for both, YoYo IR1 distance (p = 0.002) and CV values (p<0.001) with no significant changes in the SO group. 30-m sprint performance were slightly improved in the ST group with significantly decreased performance times identified in the SO group (p<0.001). Values for D' were slightly reduced in both groups (ST -44.5 m, 95% CI = -90.6 to 1.6; SO -42.6 m, 95% CI = -88.7 to 3.5). Conclusions: combining a 6-week moderate strength training with soccer training significantly improves CV, Yo-Yo IR1 whilst moderately improving 30-m sprint performances in non-previously resistance trained male soccer players. Critical Velocity can be recommended to coaches as an additional valid testing tool in soccer.